2014
DOI: 10.1007/s11095-014-1385-4
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the Physical Stability of Amorphous Indomethacin by Mixing it with Octaacetylmaltose. Inter and Intra Molecular Studies

Abstract: Acetylated derivative of maltose might be very effective agent to improve physical stability of amorphous indomethacin as well as to enhance its solubility. Intermolecular interactions between modified carbohydrate and IMC are likely to be responsible for increased stability effect in the glassy state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 92 publications
2
27
0
Order By: Relevance
“…Molecules of an excipient, which are able to specifically interact with the drug molecules, prevent the recrystallization process of the drug. 10 , 31 33 , 22 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecules of an excipient, which are able to specifically interact with the drug molecules, prevent the recrystallization process of the drug. 10 , 31 33 , 22 …”
Section: Introductionmentioning
confidence: 99%
“…Kaminska et al have shown that acMAL might be very effective in stabilizing the amorphous form of indomethacin (IMC). 22 The authors found that strong interactions between the IMC and acMAL by forming hydrogen bonds between molecules of both compounds led to the improvement in the physical stability of amorphous API even at temperatures higher than T g of the binary systems. The water solubility of amorphous IMC was also enhanced in solid dispersions with acMAL.…”
Section: Introductionmentioning
confidence: 99%
“…The δ values of IMC, Kollicoat IR, and HPMC were 24.8 MPa 1/2 (δ d = 22.2 MPa 1/2 , δ p = 6.0 MPa 1/2 , δ h = 9.4 MPa 1/2 ) [35], 32.5 MPa 1/2 [36], and 30.6 MPa 1/2 (δ d = 18.0 MPa 1/2 , δ p = 15.3 MPa 1/2 , δ h = 19.4 MPa 1/2 ) [37] based on Equations (6) and (7). Thus, the difference in solubility parameters between IMC and HPMC was calculated to be less than 7 MPa 1/2 based on Equations (6) and (7), indicating that IMC-MSNs@HPMC (F9) had the best solubility enhancement effect. As shown in Figure 5, the same result was obtained in Figure 6, where the solubility value of IMC-MSNs@HPMC (F9) was the largest.…”
Section: Permeability and Bioavailability Studiesmentioning
confidence: 99%
“…Indomethacin (IMC, Figure 1) is a non-steroidal anti-inflammatory drug used widely for relieving symptoms of fever, rheumatoid arthritis, cardiovascular and Alzheimer diseases, etc. [7]. However, the application of IMC was limited, because it belongs to BCS Class II drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Low molecular weight co-formers such as amino acids and saccharides have shown to stabilise amorphous poorly soluble drugs by generation of co-amorphous systems [21,22]. Active ingredients are also used as low molecular weight co-formers with the advantage of the co-administration of therapeutics.…”
Section: Introductionmentioning
confidence: 99%